(3EUdGM GdCOhjI GdeSgdI hfaj eVGQgG hVQhH ESJYeGdgGs - (3MHjT Hf GdMSf GdOeTbj, GdCYSe GdOeTbj , cGf MjkG bHd (B264 (3gs
(3ChdgG (B:s
(3CeG GdefaYI GdJi jfGdgG CHOGf GdfGS hfahSge ef TQH GdGOhjI GdeSgdI YfOeG jVWQhf Edi TQHgG s
(3BNQgG (B:s
(3hfaY CUMGH GdMeGjGJ GdJi Jchf ef GdeQI GdShOG hGdHdZe GdeMJQb agPG eG bUOfG HGUdGMg ef GdGOhjI s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdMGOSI YTQs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B189s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs